Analisis Sistem Penatausahaan Belanja Operasi Pada Badan Keuangan Daerah Provinsi Sumatera Barat - Dewi Sartika; Fitrah Mulyani; Andre Ilyas (Universitas Dharma Andalas, 2022)
ABSTRACT This study was conducted to analyze how the operating expenditure administration system at the regional financial agency of West Sumatra province was in accordance with the regulation of the Minister of Home Affairs number 77 of 2020. The research method carried out in this study wa a qualitative descriptive study, while the data collection techniques used library research, documentation and interviews. Based on the results of the study, it was found that regional financial agency of the province of West Sumatera has carried out and operating expenditure administration system in accordance with the applicable money regulations. As well as in submitting operating expenses using documents that have been determined, namely a letter of provision of funds, a letter of request for direct payment, a letter of order to pay, and a warrant for disbursmenet of funds. ABSTRAK Penelitian ini bertujuan untuk menganalisis bagaimana Sistem Administrasi Belanja Operasional pada Badan Keuangan Daerah Provinsi Sumatera Barat sesuai dengan Peraturan Menteri Dalam Negeri Nomor 77 Tahun 2020. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian deskriptif kualitatif. Sedangkan teknik pengumpulan data menggunakan studi kepustakaan, dokumentasi dan wawancara. Berdasarkan hasil penelitian diketahui bahwa Badan Keuangan Daerah Provinsi Sumatera Barat telah menerapkan Sistem Administrasi Belanja Operasional sesuai dengan ketentuan yang berlaku. Demikian pula dalam pengajuan Belanja Operasional menggunakan dokumen yang telah ditentukan yaitu Surat Penyediaan Dana (SPD), Surat Permintaan Pembayaran Langsung (SPP-LS), Surat Perintah Membayar (SPM-LS), dan Surat Perintah untuk Penyaluran Dana (SP2D-LS).